2019
DOI: 10.1080/10408444.2019.1579169
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory assessment and risk management of chemical mixtures: challenges and ways forward

Abstract: This paper summarizes current challenges, the potential use of novel scientific methodologies, and ways forward in the risk assessment and risk management of mixtures. Generally, methodologies to address mixtures have been agreed; however, there are still several data and methodological gaps to be addressed. New approach methodologies can support the filling of knowledge gaps on the toxicity and mode(s) of action of individual chemicals. (Bio)Monitoring, modeling, and better data sharing will support the deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
84
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(87 citation statements)
references
References 80 publications
0
84
0
3
Order By: Relevance
“…Cedergreen (2014) defined synergetic mixtures as those which elicited an observed effect that was at least 2-fold greater than the predicted effect, using concentration addition as a reference model. As reviewed extensively by Bopp et al (2019), the challenge in realistically assessing exposure to mixtures is taking into account the target population(s), the timing of exposure, or whether individuals or organisms are exposed to mixtures simultaneously or sequentially (Bopp et al 2019). Kienzler et al (2016) described current and potential future tools for modeling mixture effects but indicated that further guidance, data, and expertise are required before they can be fully applied (Kienzler et al 2016).…”
Section: Chemical Mixtures-something From Nothing?mentioning
confidence: 99%
“…Cedergreen (2014) defined synergetic mixtures as those which elicited an observed effect that was at least 2-fold greater than the predicted effect, using concentration addition as a reference model. As reviewed extensively by Bopp et al (2019), the challenge in realistically assessing exposure to mixtures is taking into account the target population(s), the timing of exposure, or whether individuals or organisms are exposed to mixtures simultaneously or sequentially (Bopp et al 2019). Kienzler et al (2016) described current and potential future tools for modeling mixture effects but indicated that further guidance, data, and expertise are required before they can be fully applied (Kienzler et al 2016).…”
Section: Chemical Mixtures-something From Nothing?mentioning
confidence: 99%
“…The wholemixture approach is frequently applied for environmental samples, as it has the advantage of assessing the toxicity of mixtures of unknown composition and unknown potential for interactions, and measures directly the combined effect of the complete mixture. Although this approach is increasingly being used in situations of unknown and varying composition, such as chemical pollutants in surface water and wastewater effluents, the whole-mixture effect data are available for a limited number of mixtures and the substances driving the overall response frequently remain unidentified as well as potential interactions amongst mixture components (Bopp et al 2019;HernĂĄndez et al 2017). Conversely, the component-based approach requires identification of the chemicals present in the mixture of concern (e.g., concentration, mode of action (MoA) and toxicity of the components of the mixture, which is often lacking) followed by mathematical modeling to predict their joint action based on information from each individual component of the mixture.…”
Section: Introduction To Chemical Mixturesmentioning
confidence: 99%
“…The missing information can be addressed using novel technologies which enable a mechanistic understanding of the combined effects or can be estimated in part using computational models (see "Mechanism-based methodologies for the evaluation of the impact of chemical mixtures on human health"). However, component-based approaches can potentially lead to underestimations of hazard when the composition of a mixture is not fully known, which is usually the case, except for clearly defined, intentionally manufactured products (e.g., pesticide formulations), or chemicals present in foodstuff (e.g., multiple residues of pesticides) (Bopp et al 2019;HernĂĄndez et al 2017).…”
Section: Introduction To Chemical Mixturesmentioning
confidence: 99%
See 2 more Smart Citations